Immunohistochemically detectable p53 and mdm-2 oncoprotein expression in colorectal carcinoma: prognostic significance. Issue 1 (February 1995) - Öfner, D; Maier, H; Riedmann, B; Holzberger, P; Nogler, M; Tötsch, M; Bankfalvi, A; Winde, G; Böcker, W; Schmid, K W
Abstract : Aims —To investigate the correlation between the expression of the p53 and mdm-2 oncoproteins and to assess their prognostic value in colorectal cancer. Methods —Using a polyclonal (CM1) and a monoclonal antibody directed against p53 and mdm-2, respectively, these oncoproteins were stained immunohistochemically in 109 colorectal adenocarcinomas. Results —p53 was detected in less than 10% of tumour cells in 11 of 109 adenocarcinomas, in 10-50% of tumour cells, in 17 of 109 adenocarcinomas, and in more than 50% of tumour cells in 32 of 109 adenocarcinomas. Expression of mdm-2 was detected in 22 of 109 (20%) cases investigated, of which 19 showed concomitant p53 expression. In most cases mdm-2 immunoreactivity was strongly associated with a small proportion of p53 positive tumour cells. Both p53 and mdm-2 expression lacked statistical significance when correlated with common staging and grading parameters. Conclusions —Detection of p53 and mdm-2 oncoprotein expression, detected using immunohistochemistry, is of no prognostic value in colorectal cancer. However, the close correlation between mdm-2 immunoreactivity and the proportion of p53 positive cells provides further evidence that the mdm-2 gene product interacts with p53 protein.